C4.5 Versus Other Decision Trees: A Review - Salih Özsoy; Gokhan Gumus; Savriddin Khalilov (Universitas Sriwijaya, 2015)
In this study, Data Mining, one of the latest technologies of the Information Systems, was introduced and Classification a Data Mining method and the Classification algorithms were discussed. A classification was applied by using C4.5 decision tree algorithm on a dataset about Labor Relations from http://archive.ics.uci.edu/ml/datasets.html. Finally, C4.5 algorithm was compared to some other decision tree algorithms. C4.5 was the one of the successful classifier.